Political parallelism and media coalitions in Western Europe - Artero, J (2015)
In this piece of research, Artero reviews previous studies and introduces the new concept of media coalitions, defined as the "assortment of media outlets explicitly or implicitly supporting a particular political party, candidate or ideology". That phenomenon is analysed regarding the last general elections of five Western European democracies: Britain, France, Germany, Spain and Italy.